A FRAM requirements analysis for Safety Differently investigations. (May 2020) - Meeuwis, C.J.; Steinmetz, V.; Hamming, J.F.; Dekker, S.W.A.
Highlights: Requirements for a Safety Differently investigation. Using FRAM for requirement analysis. Safety Differently versus Traditional safety investigation. Abstract: The present study reports on the transition of a critical incident investigator group within a University Medical Center to a Safety Differently paradigm. The most salient findings of this transition relate to the requirements that investigators themselves identify for the success of Safety Differently investigations in their institution. We conducted a FRAM (Functional Resonance Analysis Method) analysis of the requirements related to inputs, outputs, time, control, preconditions and resources for a successful Safety Differently investigation. The findings are applicable to Safety Differently investigations independent of the domain in which they might take place. The results show a critical need of training, coaching, time, human resources and commitment of institutional leaders for the transition to Safety Differently investigations.